IMPROVING THE QUALITY OF COLORS ‎Carassius auratus auratusTHROUGH ADDITION OF REBON SHRIMP FLOUR IN ‎COMMERCIAL PELET - Supri Ati; Mulyadi Mulyadi; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract This  research  was  conducted  on  March  28  –  May  7  2018,  at  the  Laboratory  of ‎Aquaculture Technology, Faculty of Fisheries and Maritime Affairs, University of Riau. The ‎purpose of this study was to determine the best dose of rebon shrimp flour in improving the color ‎quality  of comet fish. The method in this study is a 1-factor Complete Randomized Design ‎‎(RAL) experimental method with 4 levels of treatment. The fourt treatments were the addition of ‎rebon shrimp as much as 0, 25%, 35% and 45%. the main parameter observed is the increase in ‎color while the growth, survival and quality of water as supporting data. The results showed that ‎the addition of rebon shrimp had an effect on increasing the color and growth of comet fish. The ‎addition of rebon shrimp by 35% from 1 kg feed gives the best color quality improvement with ‎an average value of 6.3 on thepaper toca color finder.‎ Keywords: comet fish, rebon shrimp, color quality, commercial pellets, increase